Challenges of self-directed clinical skill learning: experience among undergraduate nursing students in Malaysia - Zainudin, Airul Azizan; Ahmad, Norfadzilah; Mohd Mohadis, Hazwani (Horizon Research Publishing, 2019)
Purpose: This study aimed to explain the challenges experienced in self-directed clinical skill learning specifically in clinical skill laboratory among undergraduate nursing students in Malaysia. Methodology: A qualitative study using in-depth interview was conducted with 16 students attending Bachelor of Nursing in one of the public universities in Malaysia. The interview was open-ended to explore the overall perspective of the participants concerning their view about the problems and challenges they experienced on the self-directed clinical skill learning. Main Findings: Three major themes have been found on self-directed clinical skill learning which are ‘lack of self-management’, ‘lack of desire for learning’ and ‘lack of self-control of learning’. The subthemes for ‘lack of self-management’ are poor time management, lack of communication with educator and lack of assessment of learning needs. The subthemes for ‘lack of desire for learning’ are not open to new ideas, lack of internal motivation, educator-dependent for seeking new knowledge and low quality of supporting learning materials. Lastly, the subtheme for ‘lack of control of learning’ is not realizing the importance of self-evaluation among undergraduate nursing students. Applications: Our findings informed academicians on various problems and challenges that occur in self-directed learning activities in clinical skill laboratory. These findings would assist them in preparing appropriate learning environment and clinical skill activities, which would improve the efficiency of knowledge and skill transfer and also enhance students’ academic performance. Novelty/Originality: Previous studies have identified many challenging factors affecting clinical skill learning among nursing students such as clinical learning environment (e.g. physical, psychosocial, organizational) and students’ learning process based on broad spectrum of perspective without highlighting student-centred point of view. Thus, in our study, we have attempted to explore how nursing students describe the challenging experience of undertaking the process of learning clinical skills from the perspective of a self-directed learner.